Carbide-reinforced NiMnSn shape memory alloy composites: fabrication and thermal, microstructural, magnetic properties - Sariates, Dine; Kok, Mediha (Springer, 2025)
NiMnSn magnetic shape memory alloys are a preferred alloy group due to their lower cost compared to NiMn-based alloys with similar properties. However, the brittle nature of these alloys limits their application. In this study, it is aimed to strengthen NiMnSn alloy with high strength boron carbide (B4C), silicon carbide (SiC), and titanium carbide (TiC) additives. In DSC analysis, martensite transformation temperatures decreased in all doped alloys; especially in the SiC-doped alloy, the transformation temperature decreased to approximately 255 K. According to the thermogravimetric analysis results, the lowest oxidation rate was observed in the B4C doped alloy (5.26 x 1015 g.s-1) and the highest in the TiC-doped alloy (8.40 x 1015 g.s-1). As a result of XRD analysis, the crystallite size increased with doping; while the pure NiMnSn alloy was 40 nm, this value increased to 134 nm with SiC doping. At the same time, Vickers microhardness values also increased significantly; the value of 187.5 Hv in the undoped alloy reached 370.4 Hv with SiC doping. Magnetic measurements by PPMS showed that the saturation magnetization of the SiC-doped alloy at 300 K was about 29 emu g-1, while this value was only 7-8 emu g-1 in the martensite phase alloys. These results reveal that carbide doping significantly improves the thermal, mechanical, and magnetic properties of NiMnSn alloys.
Keywords: NiMnSn alloy; Carbide reinforced; Magnetization; Magnetothermal behavior